Leaves of Quercus ilex as Indicators of Airborne Trace Element Distribution in Lucca (Central Italy) - Francini, A.; Lorenzini, G.; Nali, C.; Loppi, S. (II INTERNATIONAL CONFERENCE ON LANDSCAPE AND URBAN HORTICULTURE, 2010)
Ambient air has always contained particles, ranging from sub-micrometric aerosols to clearly visible dust and sand grains. Plants have evolved to maximise light interception and CO2 assimilation and, as a consequence, they are also highly efficient receptors of airborne pollutants. The use of plant tissues has since long been shown to be an effective indicator of metal air pollution. Leaves of the evergreen species Quercus ilex were used as a passive sampler to describe the distribution of selected elements in the area around the walls of Lucca (Central Italy). Unwashed healthy mature leaves collected in June 2006 from 16 sampling sites were analysed by ICP-MS for Al, Ba, Be, Bi, Br, Ca, Cd, Cl, Co, Cr, Cs, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Si, Ti, V and Zn. Values were normalised by subtracting baseline concentrations of biologically essential elements coming from Q. ilex plants collected into Botanical Garden of Lucca. Enrichment factors (EF) were calculated taking Al as crustal reference element. Cd, Cu and Zn exhibited the highest EF, with values ranging between 100 and 1000. Varimax rotated factor analysis allowed identifying three main source groups of elements, namely crustal components, sea-salt spray and anthropogenic sources (vehicular traffic, industrial activities). The factor one (crustal components) explained 48.3% of the total variance. Common high loadings for this factor were Al, Bi, Br, Co, Cu, Fe, Si, V, and Zn, which indicate a predominant soil contribution. Results are discussed with emphasis on the potential role of vegetation for the removal of particulate pollution.
The following values have no corresponding Zotero field: periodical: II INTERNATIONAL CONFERENCE ON LANDSCAPE AND URBAN HORTICULTURE pub-location: 999 RIVERVIEW DR, STE 208, TOTOWA, NJ 07512-1165 USA
Keywords: enrichment factor; factor analysis; ICP-MS; pollution

Effects of urban heavy metal pollution on organic matter decomposition in Quercus ilex L. Woods - Cotrufo, M. F.; Santo, A. V. De; Alfani, Anna (Environmental Pollution, 1995)
Decomposition of oak (Quercus ilex) leaves containing different concentrations of Fe, Zn, Cu, Cr, Ni and Pb was measured in laboratory microcosms. The leaves were collected from a polluted site inside the city of Naples and from a control site away from the city. Soil was sampled from the upper A horizon (0-5 cm) at both sites and analyzed for respiration, microbial biomass and abundance of fungal mycelia. The soils from the two sites differed significantly in heavy metals concentrations. The accumulated mass loss reached an asymptotic value after four months both for the control and polluted litters. However, control and polluted litters significantly differed in accumulated mass loss, that was respectively 40 % and 29 % of the initial weight, after 10 months. Moreover decomposition rates appeared to be strongly influenced by metal contamination in the early stages, while in later stages, they did not differ significantly. Litter respiration appeared to be inhibited by metal contamination and showed pattern and rates consistent with those found for litter decomposition. Fungal mycelia were significantly less abundant both in litter and soil from the polluted site than from the con- trol site. Metabolic activity (both as soil respiration and degree of mineralization) was lower in the polluted soil. Soil respiration and amount of soil mycelia correlated negatively with soil Pb, Zn and Cr concentration.
Keywords: Fungal biomass (voyant9; Heavy metals; litter decomposition; pollution; Soil microbial biomass; Soil respiration

Modelling the long-term impacts of atmospheric pollution deposition and repeated forestry cycles on stream water chemistry for a holm oak forest in northeastern - Neal, C; Avila, a; Rodà, F (Journal of Hydrology, 1995)
Estimates based on the MAGIC model of the long-term effects on stream water quality of forest management cycles as well as of atmospheric pollutant inputs for a holm oak catchment in northeastern Spain, show that despite high pollutant sulphur inputs as well as substantial base cation loss from the catchment owing to forest harvesting, stream water has not deteriorated in any major way. Acidification of the catchment will continue, to a limited degree, unless either sulphur deposition is reduced by more than 60% or forest harvesting schemes are terminated. The detrimental changes in water quality owing to acid deposition and forestry harvesting practice in other parts of Europe are not observed in this region, because of high base inputs from the atmosphere and high base cation weathering rates within the catchment.
Keywords: atmospheric deposition; forestry practices (voyant); pollution; soil chemistry; stream water chemistry

New type of damage to Quercus ilex: pollen germination and hydration ability - Bellani, Lorenza M.; Paoletti, E. (European Journal of Forest Pathology, 1992)
Pollen grains collected from trees of Quercus ilex L. belonging to different classes of new type damage were analyzed. Five parameters were taken into account: viability, germinability, tube lengthening, grain volume of the dehydrated state and after rehydration. Damage to mother plants clearly influences the above mentioned parameters, causing a reduction in pollen grain viability, germinability, and in the ability of the grains to rehydrate.
Keywords: damage; germination (voyant); pollen; pollution; viability

Evergreen oak leaves as natural monitor in environmental pollution - Capannesi, G; Caroli, S; Rosada, A (Journal of radioanalytical and nuclear chemistry, 1988)
Evergreen oak was chosen as a possible biological monitor of environmental pollution. It was shown that there is a direct relationship between the concentration of elements in leaves and the presence of pollution sources, i.e. the density of vehicular traffic.
Keywords: Elemental analysis; leaves (voyant); pollution